Hubungan Usia dan Paritas dengan Kejadian Ketuban Pecah Dini pada Ibu Bersalin di Rumah Sakit Harapan Bunda Kota Batam - Ratika Lelo Yasinta; Catur Yulinawati; Yulia Devi Putri (Detector: Jurnal Inovasi Riset Ilmu Kesehatan, 2025)
Premature rupture of membranes (KPD) is the rupture of the membranes before there are signs of labor, and after waiting for an hour the signs of labor have not yet begun. The time from when the membranes rupture until uterine contractions occur is called premature rupture of membranes. Factors that are closely related to PROM include infection, socio-economic factors, blood type factors, smoking behavior, history of PROM, incompetent cervix and intrauterine enhancement that is high or excessively high, fetal disproportion, multigravidity, multiple pregnancies, previous history of PROM , polyhydramnios, trauma, age and parity. The danger of premature rupture of membranes is the possibility of infection in the uterus and premature birth which can increase morbidity and mortality for mother and baby. Premature rupture of membranes causes a direct connection between the outside world and the space in the uterus, making it easier for infection to occur. The aim of this study is to determine the relationship between age and parity with the incidence of premature rupture of membranes in women giving birth at Harapan Bunda Hospital, Batam City in 2023. This research design uses analytical observational with a cross sectional approach, where data is taken using secondary data with a sample size of 65 people. The processing technique uses the chi-square test. The data obtained from the results of statistical tests is with p-value for age = 0.028 and for parity p-value = 0.039. The conclusion of this research is that the majority of mothers give birth at a non-risk age (20-35) and at a parity that is not at risk (2-3). There is a relationship between the age and parity of mothers giving birth and the incidence of KPD at Harapan Bunda Hospital, Batam City in 2023. With the p-value is 0.028 for age and the p-value is 0.039 for parity so that the p-value < α (0.05).